Evaluasi Pemanfaatan Laboratorium Fisika Pasca Pelaksanaan Program Aklam Mahasiswa Pendidikan Fisika UIN Alauddin Makassar - Suhardiman; Rafiqah; Anas Irwan; Ayyub Ibrahim; Ahmad Purwadi Kerans (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
The aims of the study were: 1) to find out the description of the management of school laboratories after the application of student laboratory work (AKLAM) for the Physics Education study program at UIN Alauddin Makassar in the Gowa and Jeneponto regions; 2) To find out an overview of the use of school laboratories after the student laboratory work application (AKLAM) of the Physics Education study program at UIN Alauddin Makassar in the Gowa and Jeneponto regions; 3) To find out what contribution the school has obtained after implementing the Student Laboratory Work Application (AKLAM) for the physics education study program at UIN Alauddin Makassar in the Gowa and Jeneponto regions. This research method is Mixed Methods by combining qualitative and quantitative research. The results of the analysis obtained are: 1) post-AKLAM governance is still quite in accordance with school laboratory standards; 2) for the use of post-AKLAM laboratories, namely the use of the laboratory as a practicum place is still maintained; 3) the contributions obtained by each post-AKLAM school are almost the same including laboratory improvements and student guidance.